STRATEGI PEMERINTAH DESA DALAM PENINGKATAN PEMBERDAYAAN MASYARAKAT DESA PRAPAT TUNGGAL KECAMATAN BENGKALIS KABUPATEN BENGKALIS 2021-2022 - Suganda, Anggun; ', Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This research is motivated by the increasingly developing mindset of the community in carrying out activities to build community independence by using the capabilities they have. So in life, an effort is needed to fulfill daily living needs, namely by utilizing natural resources, such as the use of marine products and the use of plantations such as sago trees, which are processed into a product, namely shrimp paste, shrimp crackers, fish crackers and sago crackers which are become a business for the people of Prapat Tunggal Village, Bengkalis Regency. The problem formulation in this research aims to determine the actions of the village government in developing Micro, Small and Medium Enterprises (UMKM) and Food and Animal Security as well as to determine the impact of empowering Micro, Small and Medium Enterprises (UMKM) and food and animal security in increasing community income in Prapat Tunggal Village, Bengkalis Regency. Results in this research the author uses the legal theory of governance from Aminudin Ilmar. The object of this research is the Village Government's strategy for increasing community empowerment in Prapat Tunggal Village, Bengkalis Regency 2021-2022. To find the results in this research the author used primary data and secondary data, the data collection techniques used were interviews and documentation. The research results show that the Village Government has a very important role in increasing community empowerment, one of which is in the fields of UMKM and Food and Animal Security. Keywords: Enabling, Strengthening, Protection, Support, Maintenance